Carbodiphosphorane mediated synthesis of a triflyloxyphosphonium dication and its reactivity towards nucleophiles. Issue 20 (23rd February 2017) - Yogendra, S.; Hennersdorf, F.; Bauzá, A.; Frontera, A.; Fischer, R.; Weigand, J. J.
Abstract : Synthesis of the triflyloxyphosphonium dication is presented bearing two electrophilic sites which are selectively addressable by different nucleophiles. Abstract : A carbodiphosphorane ((Ph3 P)2 C) mediated synthesis of the first triflyloxyphosphonium dication (1 2+ ) bearing two electrophilic sites is presented. Depending on the nucleophile, 1 2+ reacts selectively either at the sulfur atom of the triflyloxy moiety or at the directly attached phosphorus atom. In substitution reactions at the phosphorus atom the triflyloxy moiety serves as a leaving group and enables the synthesis of rare examples of pseudo-halophosphonium dications.